Data from: Rapid sex-specific evolution of age at maturity is shaped by genetic architecture in Atlantic salmon ... - Czorlich, Yann; Aykanat, Tutku; Erkinaro, Jaakko; Orell, Panu; Primmer, Craig R. (Dryad, 2019)
Understanding the mechanisms by which populations adapt to their environments is a fundamental aim in biology. However, it remains challenging to identify the genetic basis of traits, provide evidence of genetic changes and quantify phenotypic responses. Age at maturity in Atlantic salmon represents an ideal trait to study contemporary adaptive evolution as it has been associated with a single locus in the vgll3 region, and has also strongly changed in recent decades. Here, we provide an empirical example of contemporary adaptive evolution of a large effect locus driving contrasting sex-specific evolutionary responses at the phenotypic level. We identified an 18% decrease in the vgll3 allele associated with late maturity (L) in a large and diverse salmon population over 36 years, induced by sex-specific selection during the sea migration. Those genetic changes resulted in a significant evolutionary response in males only, due to sex-specific dominance patterns and vgll3 allelic effects. The vgll3 allelic and ... : Adults dataData associated with the article: Czorlich Y., Aykanat T., Erkinaro J., Orell P. & Primmer C.R. (2018) Rapid sex-specific evolution of age at maturity is shaped by genetic architecture in Atlantic salmon. Nature Ecology & Evolution. Table including the genotypes of adults (row) at 190 loci and additional informations (e.g. spawning year, sex)Adults_data.xlsxJuveniles_dataData associated with the article: Czorlich Y., Aykanat T., Erkinaro J., Orell P. & Primmer C.R. (2018) Rapid sex-specific evolution of age at maturity is shaped by genetic architecture in Atlantic salmon. Nature Ecology & Evolution. Table including the genotypes of juveniles (row) at 190 loci and additional informations (population and sex)Drift estimated with a Wright-Fisher approximationCode used in Czorlich Y., Aykanat T., Erkinaro J., Orell P. & Primmer C.R. (2018) Rapid sex-specific evolution of age at maturity is shaped by genetic architecture in Atlantic salmon. Nature Ecology & Evolution. It ...